Microvascular lung vessels obstructive thromboinflammatory syndrome in patients with COVID-19: Insights from lung intravascular optical coherence tomography - Hajjar, Ludhmila Abrahão; Ancona, Marco B.; Filho, Roberto Kalil; Tresoldi, Moreno; Caldas, José Guilherme; Monti, Giacomo; Carnevale, Francisco Cesar; De Cobelli, Francesco; Moreira de Assis, André; Ciceri, Fabio; Landoni, Giovanni; Dijkstra, Jouke; et al. (Frontiers in Medicine, 2023)
Background Microvascular lung vessels obstructive thromboinflammatory syndrome has been proposed as a possible mechanism of respiratory failure in COVID-19 patients. The aim of the present study is to assess the safety, tolerability and diagnostic value of Optical Coherence Tomography (OCT) for pulmonary microvascular thromboinflammatory syndrome assessment in patients with COVID-19 pneumonia. Methods The COVID-OCT trial is a multicenter, open label, prospective, interventional clinical study. Two cohorts of patients were included in the study and underwent pulmonary OCT evaluation. In Cohort A, patients with COVID-19 with negative CT scan for pulmonary thrombosis and increased thromboinflammatory markers (D-Dimer > 10,000ng/mL or 5,000 < D-dimer < 10,000 ng/mL and either C Reactive Protein > 100 mg/dL or IL-6 > 6 pg/mL or ferritin > 900 ng/L) were included in the trial. In Cohort B, patients with COVID-19 and CT scan positive for pulmonary thrombosis were included in the trial. The primary endpoints of the study were: i) to evaluate the overall safety of OCT investigation in COVID-19 pneumonia patients; ii) to report the potential usefulness of OCT as a novel diagnostic tool for the diagnosis of microvascular pulmonary thrombosis in COVID-19 patients. Results A total of 13 patients were enrolled. A mean of 6.1  2.0 OCT runs were performed in each patient, both in ground glass, achieving a good evaluation of distal pulmonary arteries. Overall, OCT runs identified microvascular thrombosis in 8 patients (61.5%): 5 cases of red thrombus, 1 case of white thrombus and 2 cases of mixed. In Cohort A, the minimal lumen area was 3.5 ± 4.6mm2 with a % area stenosis of 60.9 ± 35.9 and the mean length of thrombus-containing lesion was 5.4 ± 3.0 mm. In Cohort B the % area obstruction was 92.6±2.6 and the mean thrombus-containing lesion length was 14.1±13.9mm. No peri-procedural complications occurred in the 13 patients. Conclusions OCT seems safe and accurate in evaluating the distal pulmonary arteries in hospitalized COVID-19 patients, allowing the first in vivo documentation of distal pulmonary arterial thrombosis in patients scan for pulmonary embolism and increased thromboinflammatory markers even when angioCT was negative for pulmonary thrombosis.